Thai Visitors’ Street Food Motivation Influencing Destination Loyalty: The Case Study of Bangkok - Chaowanasilp, Warit; Agmapisarn, Charoenchai (Journal of Business, Innovation and Sustainability (JBIS), 2023)
Food is part of a visitor’s experience and is used as a marketing tool for tourism. Few studies have attempted to separate and examine the role played by street foods to the destination loyalty of visitors. Hence, this study evaluated Thai visitors’ street food motivation and its influence on destination (Bangkok) loyalty. Moreover, the study proposed a structural model addressing the potential relationships between visitors’ street food motivation, street food perception, street food experience, street food satisfaction, and destination loyalty among Thai visitors in Bangkok. Questionnaires were collected from 356 Thai visitors and obtained by simple random sampling. The data were analyzed by SPSS and partial least squares-structural equation modelling by SmartPLS 3.0. The results found indirect influences of visitors’ street food motivation on destination loyalty. Thus, entreprenuers, government agencines, and other involved agencies can utilize street food as a sustainable marketing tool to maintain and attract Thai visitors.